Verapamil inhibits efflux pumps in Candida albicans, exhibits synergism with fluconazole, and increases survival of Galleria mellonella - Vega-Chacón, Yuliana [UNESP] (2021)
The emergence of resistance requires alternative methods to treat Candida albicans infections. We evaluated efficacy of the efflux pump inhibitor (EPI) verapamil (VER) with fluconazole (FLC) against FLC-resistant (CaR) and -susceptible C. albicans (CaS). The susceptibility of both strains to VER and FLC was determined, as well as the synergism of VER with FLC. Experiments were performed in vitro for planktonic cultures and biofilms and in vivo using Galleria mellonella. Larval survival and fungal recovery were evaluated after treatment with VER and FLC. Data were analyzed by analysis of variance and Kaplan-Meier tests. The combination of VER with FLC at sub-lethal concentrations reduced fungal growth. VER inhibited the efflux of rhodamine 123 and showed synergism with FLC against CaR. For biofilms, FLC and VER alone reduced fungal viability. The combination of VER with FLC at sub-lethal concentrations also reduced biofilm viability. In the in vivo assays, VER and FLC used alone or in combination increased the survival of larvae infected with CaR. Reduction of fungal recovery was observed only for larvae infected with CaR and treated with VER with FLC. VER reverted the FLC-resistance of C. albicans. Based on the results obtained, VER reverted the FLC-resistance of C. albicans and showed synergism with FLC against CaR. VER also increased the survival of G. mellonella infected with CaR and reduced the fungal recovery.